2019
DOI: 10.3390/ijerph16162897
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Annatto Tocotrienol Supplementation on Cartilage and Subchondral Bone in an Animal Model of Osteoarthritis Induced by Monosodium Iodoacetate

Abstract: Osteoarthritis is a degenerative joint disease which primarily affects the articular cartilage and subchondral bones. Since there is an underlying localized inflammatory component in the pathogenesis of osteoarthritis, compounds like tocotrienol with anti-inflammatory properties may be able to retard its progression. This study aimed to determine the effects of oral tocotrienol supplementation on the articular cartilage and subchondral bone in a rat model of osteoarthritis induced by monosodium iodoacetate (MI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 48 publications
2
27
0
Order By: Relevance
“…OA was induced in SD rats; we employed the method of Wang with minor modifications [ 32 ]. After anesthetization with injection of Zoletil mixture (Vibrac, France) 0.75 mg/kg intraperitoneally, rats were injected with MIA 80 mg/mL in a 50 μ L volume using a 0.3 mL insulin syringe (31G needle) inserted through the patellar ligament into the intra-articular space of the right knee; normal rats were injected with an equivalent volume of saline [ 33 ]. The rats in all groups were sacrificed after the end of experimental period.…”
Section: Methodsmentioning
confidence: 99%
“…OA was induced in SD rats; we employed the method of Wang with minor modifications [ 32 ]. After anesthetization with injection of Zoletil mixture (Vibrac, France) 0.75 mg/kg intraperitoneally, rats were injected with MIA 80 mg/mL in a 50 μ L volume using a 0.3 mL insulin syringe (31G needle) inserted through the patellar ligament into the intra-articular space of the right knee; normal rats were injected with an equivalent volume of saline [ 33 ]. The rats in all groups were sacrificed after the end of experimental period.…”
Section: Methodsmentioning
confidence: 99%
“…Both γT3 and δT3 were capable of decreasing inflammation (reduced CRP and TNF-α) and oxidative stress (increased SOD and total glutathione (GSH)) in the CIA rats [169,170]. A recent study showed that annatto tocotrienol at 100 mg/kg prevented cartilage degeneration in a rat model of osteoarthritis induced by monosodium iodoacetate, as evidenced by reduced histological scoring and circulating cartilage oligomeric matrix protein level in the treated rats [171]. Taken together, findings from these studies suggested that T3 may be effective in protecting against arthritis-induced joint damage (Table 10).…”
Section: Effects Of Tocotrienol On Arthritismentioning
confidence: 99%
“…45 In an animal model of OA, it was shown that supplementation with annatto-derived tocotrienol (100 mg/kg) prevented cartilage degradation, which may prevent the progression of OA. 46…”
mentioning
confidence: 99%